Production of Alkaline Cellulase by Fungi Isolated from an Undisturbed Rain Forest of Peru. (19th November 2012) - Vega, Karin; Villena, Gretty K.; Sarmiento, Victor H.; Ludeña, Yvette; Vera, Nadia; Gutiérrez-Correa, Marcel
Abstract : Alkaline cellulase producing fungi were isolated from soils of an undisturbed rain forest of Peru. The soil dilution plate method was used for the enumeration and isolation of fast growing cellulolytic fungi on an enriched selective medium. Eleven out of 50 different morphological colonies were finally selected by using the plate clearing assay with CMC as substrate at different pH values. All 11 strains produced cellulases in liquid culture with activities at alkaline pH values without an apparent decrease of them indicating that they are true alkaline cellulase producers. Aspergillus sp. LM-HP32, Penicillium sp. LM-HP33, and Penicillium sp. LM-HP37 were the best producers of FP cellulase (>3 U mL −1 ) with higher specific productivities (>30 U g −1 h −1 ). Three strains have been found suitable for developing processes for alkaline cellulase production. Soils from Amazonian rain forests are good sources of industrial fungi with particular characteristics. The results of the present study are of commercial and biological interest. Alkaline cellulases may be used in the polishing and washing of denim processing of the textile industry.